Synthesis of Some New Schiff Bases and Reaction with Urea & Thiourea Derivatives from 2-Amino -1,3,4-thiadiazole-5-thiol (Journal of the College of Basic Education, 2022)
In this paper new Schiff bases and tetrazole derivatives of 2-Amino-1,3,4-thiadiazole- 5-thiol have been prepared.2-Amino-1,3,4-thiadiazole-5-thiol was prepared by the reaction of thiosemicarbazide with carbon disulfide in alcoholic sodium carbonate solution .The new Schiff bases derivatives [2_5] were prepared by condensation of aldehyde group with 2-Amino-1,3,4-thiadiazole-5-thiol (P-Nitrobenzeldehyde ,M- Nitrobenzeldehyde, P-Hydroxybenzeldehyde, , 4-Hydroxy 3-Methoxy benzeldehyde) . The resulting Shiffbase wereReaction with acetic anhydride [6-9] and this derivatives reaction with urea and thiourea intetrahydrofuran{10-17}.All new synthesized derivatives were identified by their melting points, and FT-IR,U.V spectra. Some products were identified in elemental analysis and Chledal analysis .They have long been known to possess hypnotics activities and it is hoped that our compounds would do so.